2007
DOI: 10.1167/7.2.9
|View full text |Cite
|
Sign up to set email alerts
|

The case for the visual span as a sensory bottleneck in reading

Abstract: The visual span for reading is the number of letters, arranged horizontally as in text, that can be recognized reliably without moving the eyes. The visual-span hypothesis states that the size of the visual span is an important factor that limits reading speed. From this hypothesis, we predict that changes in reading speed as a function of character size or contrast are determined by corresponding changes in the size of the visual span. We tested this prediction in two experiments in which we measured the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
183
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(209 citation statements)
references
References 49 publications
20
183
5
1
Order By: Relevance
“…Here, the concept of the visual span (the number of characters that can be identified in a single fixation) plays a unifying role. Increased print size decreases this span [14] and suggests a decrease in reading rate. Further work, perhaps facilitated by a regression protocol similar to ours, is needed to investigate the relationship between possible declining visual span in older adults and declining reading rates.…”
Section: Discussionmentioning
confidence: 97%
“…Here, the concept of the visual span (the number of characters that can be identified in a single fixation) plays a unifying role. Increased print size decreases this span [14] and suggests a decrease in reading rate. Further work, perhaps facilitated by a regression protocol similar to ours, is needed to investigate the relationship between possible declining visual span in older adults and declining reading rates.…”
Section: Discussionmentioning
confidence: 97%
“…2 in Legge & Bigelow, 2011). For example, Legge et al (1985) showed a maximum reading speed of about 250 words/min for drifting text with over 94 % contrast, while Legge et al (2007) reported about 1,000 words/min for RSVP text with 90 % contrast. Other factors that could affect reading performance are differences in the text materials (sentences in the previous studies vs. a sequence of three-character isolated words in ours) and language (English vs. Japanese).…”
Section: Words (Filled and Open Circles) Figure 4 Also Includes The mentioning
confidence: 94%
“…Some researchers (Wolverton & Zola, 1983;Reichle et al, 1998) determined that it is 5-9 characters. Brysbaert et al (2005) argues that it is 1-18 letters while Legge et al (2007) suggests that it differs from 6 to 7 at an accuracy of 80%.…”
Section: Volume 5 Issue 4 December 2017mentioning
confidence: 99%